2006
DOI: 10.1007/s11745-006-5040-7
|View full text |Cite
|
Sign up to set email alerts
|

Human milk fatty acid composition from nine countries varies most in DHA

Abstract: Many published studies of breast milk FA composition are limited to populations from one or two countries. We aimed to examine the degree to which FA compositions vary across a number of diverse populations. Because diet and maternal adipose stores influence breast milk FA composition, differences in FA composition between groups most likely reflect habitual dietary differences. Approximately 50 breast milk samples (full breast expression) were collected from women in Australia, Canada, Chile, China, Japan, Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

48
243
9
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(312 citation statements)
references
References 33 publications
(26 reference statements)
48
243
9
3
Order By: Relevance
“…As previously discussed, low values of milk 22:6n-3 are best explained by the lack of 22:6n-3 in the diet rather than the inability of primates to secrete more 22:6n-3 into milk. Percent composition of milk 20:4n-6 in mountain gorillas (2.08%) was nearly five times the mean of published human populations Gibson and Kneebone, 1981;Koletzko et al, 1992;Yuhas et al, 2006), despite similar values for percent composition of 18:2n-6 in milk. As compared to humans and other nonhuman primates, mountain gorilla milk appears to be unique in its 20:4n-6 composition.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…As previously discussed, low values of milk 22:6n-3 are best explained by the lack of 22:6n-3 in the diet rather than the inability of primates to secrete more 22:6n-3 into milk. Percent composition of milk 20:4n-6 in mountain gorillas (2.08%) was nearly five times the mean of published human populations Gibson and Kneebone, 1981;Koletzko et al, 1992;Yuhas et al, 2006), despite similar values for percent composition of 18:2n-6 in milk. As compared to humans and other nonhuman primates, mountain gorilla milk appears to be unique in its 20:4n-6 composition.…”
Section: Discussionmentioning
confidence: 68%
“…Percent composition of LCPUFA (and their n-6/n-3 precursors) varies widely in human milk as a result of dietary differences within and among populations Yuhas et al, 2006). In a meta-analysis of 65 studies including a total of 2474 women, Brenna et al (2007) found that the percent composition of 22:6n-3 in milk ranged from 0.06-1.4%, the highest values from coastal populations with a marine-based diet.…”
Section: Discussionmentioning
confidence: 99%
“…0 g DHA/100 g total fatty acids in the milk fat of women who are not taking DHA supplements (Innis & King, 1999;Friesen & Innis, 2006). This range in mean values is similar across different countries (Innis, 1992(Innis, , 2004Jensen, 1999;Yukas et al 2006). Assuming an average of 3 .…”
Section: Maternal Dietary Lipids and Their Effect On The Composition mentioning
confidence: 87%
“…07 in milk fat from women in some areas of Africa to 1 . 0 in milk fat of women in Japan (Innis, 2004;Yukas et al 2006). In the study centre in Vancouver lactating women who exclusively breast-feed their healthy term infants and consume about 81 mg DHA/d have 0 .…”
Section: Maternal Dietary Lipids and Their Effect On The Composition mentioning
confidence: 99%
“…We have shown a linear relationship between the level of DHA in milk and the amount in the maternal diet (Gibson et al, 1997). In contrast, the level of AA in breast milk from around the world seems to be independent of a large range of diets (Yuhas R et al, 2006). What has changed in recent years is the level of LA in breast milk as omega 6 polyunsaturated fats increasingly become part of our everyday diets.…”
mentioning
confidence: 84%